Mediasi Tiongkok dalam Normalisasi Hubungan Diplomatik Iran-Arab Saudi 2023 - Abdullah, Abdullah (Global and Policy Journal of International Relations, 2025)
ABSTRACT The bilateral relations between Saudi Arabia and Iran are characterized by turmoil. Tensions reached a peak in 2016 with the execution of Nimr Al-Nimr, a Shia cleric, which sparked the arson of the Saudi Arabian embassy in Iran and severed diplomatic relations between the two countries. This conflict is rooted in differences in political views that have caused regional polarization and geopolitical instability in the Middle East, as well as having an impact on global economic stability related to oil supplies. Even though other countries' diplomatic efforts failed, the People's Republic of China (PRC) succeeded in becoming a mediator in normalizing relations between Saudi Arabia and Iran in 2023. China plays an important role as a mediator in efforts to reduce tensions between Iran and Saudi Arabia. This article examines the mediator role played by China during the dispute resolution process in diplomatic relations between the two countries. In this process, China succeeded in facilitating dialogue between the two countries, focusing on strategies, goals, interests and challenges faced during the mediation process. Research findings show that China's involvement contributed significantly to building trust between countries in conflict, thereby successfully convincing both parties. to normalize diplomatic relations. Keywords: Arab Saudi, Iran, Mediation, Normalization, China ABSTRAK Hubungan bilateral Arab Saudi dan Iran diwarnai oleh gejolak yang cenderung terlihat sebagai persaingan dan konflik. Ketegangan mencapai puncaknya pada tahun 2016 dengan eksekusi Nimr Al-Nimr, seorang ulama Syiah, yang memicu pembakaran terhadap kedutaan Arab Saudi di Iran dan memutus hubungan diplomatik kedua negara. Konflik ini berakar pada perbedaan pandangan politik yang menyebabkan polarisasi regional dan ketidakstabilan geopolitik di Timur Tengah, serta berdampak pada stabilitas ekonomi global terkait pasokan minyak. Meskipun upaya diplomatik negara- negara lain gagal, Republik Rakyat Tiongkok (RRT) berhasil menjadi mediator dalam normalisasi hubungan Arab Saudi dan Iran pada tahun 2023.Tiongkok memainkan peran penting sebagai mediator dalam upaya meredakan ketegangan antara Iran dan Arab Saudi. Artikel ini menelaah peran mediator yang dijalankan Tiongkok selama proses penyelesaian sengketa dalam hubungan diplomatik kedua negara. Dalam proses tersebut Tiongkok berhasil memfasilitasi dialog antara kedua negara tersebut, dengan fokus pada strategi, tujuan, kepentingan dan tantangan yang dihadapi selama proses mediasi. Temuan penelitian menunjukkan bahwa keterlibatan Tiongkok berkontribusi secara signifikan dalam membangun kepercayaan antar negara yang berkonflik, hingga berhasil meyakinkan kedua belah pihak untuk menormalisasi hubungan diplomatik. Kata Kunci: Arab Saudi, Iran, Mediasi, Normalisasi, Tiongkok